Managerial communication : strategies and applications - Veltsos, Jennifer R.; Hynes, Geraldine E. (Thousand Oaks, California : Sage Publications, Inc, 2025)
"Managerial Communication: Strategies and Applications focuses on communication skills and strategies that managers need to be successful in today's workplace. Known for its holistic overview of communication, solid research base, and focus on managerial competencies, this text continues to be the market leader in the field. In the Ninth Edition, authors Jennifer R. Veltsos and Geraldine E. Hynes provide coverage of cutting edge topics like managing hybrid and virtual teams, ChatGPT and artificial intelligence, and empathic listening"-- Provided by publisher.
Geraldine E. Hynes appears as the first named author on earlier editions.
Includes bibliographical references (pages 433-469) and index.
Keywords: Communication in management; Business communication